2017
DOI: 10.1016/j.vascn.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac voltage-gated ion channels in safety pharmacology: Review of the landscape leading to the CiPA initiative

Abstract: Voltage gated ion channels are central in defining the fundamental properties of the ventricular cardiac action potential (AP), and are also involved in the development of drug-induced arrhythmias. Many drugs can inhibit cardiac ion currents, including the Na current (I), L-type Ca current (Ica-L), and K currents (I, I, I, and I), and thereby affect AP properties in a manner that can trigger or sustain cardiac arrhythmias. Since publication of ICH E14 and S7B over a decade ago, there has been a focus on drug e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 140 publications
1
30
0
Order By: Relevance
“…The effect of drugs on cardiac repolarization-through assessment of the QT interval of the electrocardiogram (ECG)-is an important tool in the assessment of the propensity of novel medical products to induce arrhythmias, which has been a major cause of drug withdrawals from the market or clinical development. [1][2][3][4] Clinical and pharmacological studies have indicated that the vulnerability to induced arrhythmias varies throughout the day. 5,6 Regulation of cardiac function by diurnal factors enables efficient coupling of physiological response to anticipated environmental demand.…”
mentioning
confidence: 99%
“…The effect of drugs on cardiac repolarization-through assessment of the QT interval of the electrocardiogram (ECG)-is an important tool in the assessment of the propensity of novel medical products to induce arrhythmias, which has been a major cause of drug withdrawals from the market or clinical development. [1][2][3][4] Clinical and pharmacological studies have indicated that the vulnerability to induced arrhythmias varies throughout the day. 5,6 Regulation of cardiac function by diurnal factors enables efficient coupling of physiological response to anticipated environmental demand.…”
mentioning
confidence: 99%
“…These molecular determinants highlight a complexity that may guide future work on open state block specificity. In addition, our results exemplify the need to use CiPA guidelines when assessing clinically promising drugs [19].…”
Section: Introductionmentioning
confidence: 62%
“…As a result, the re-classification of R -roscovitine as a Class VI antiarrhythmic agent was recently proposed due to its selective non-peak block of the late I Ca,L current, which likely averts cardiac arrhythmias [59,60]. Such compensatory mechanisms are now sought after, with the CiPA guidelines recommending that all drugs be screened not only against hERG but also for L-type calcium channel and sodium channel block [19]. Thus, revisiting drugs that were deemed clinically unsafe due to hERG block, but exhibit compensatory drug actions, may yield new pharmaceutical therapeutics and will support the CiPA initiative on proarrhythmia risk assessments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional references are provided. [64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82]…”
Section: The Comprehensive In Vitro Proarrhythmia Assaymentioning
confidence: 99%